2019
DOI: 10.7759/cureus.5984
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intra-orbital Arteriovenous Fistula: A Rare Cause of Proptosis

Abstract: A left orbital arteriovenous fistula (AVF) is diagnosed in a patient presenting with proptosis. Intra-orbital AVFs are rare according to the literature search, and therefore, the best treatment modality remains controversial. We present a case of a patient who presented with non-specific symptoms. He was diagnosed with intra-orbital AVF and underwent a trans-arterial embolization. The procedure was complicated by the central retinal artery occlusion, which is one of the most feared complications associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…AVF, unlike AVMs, begins with a single contact between an artery and a vein but no nidus. 1 , 6 , 7 Intra-orbital AVFs are most usually caused by a physical lesion to the ethmoid artery, such as a fracture of the ethmoid bone and a rupture in the ocular venous system. 6 , 7 Fistulas can develop rapidly in non-traumatic situations due to artery degeneration caused by atherosclerosis, hypertension, or other vascular disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AVF, unlike AVMs, begins with a single contact between an artery and a vein but no nidus. 1 , 6 , 7 Intra-orbital AVFs are most usually caused by a physical lesion to the ethmoid artery, such as a fracture of the ethmoid bone and a rupture in the ocular venous system. 6 , 7 Fistulas can develop rapidly in non-traumatic situations due to artery degeneration caused by atherosclerosis, hypertension, or other vascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The use of trans-venous or trans-arterial embolization has yielded positive outcomes. 6 , 9 Wang et al 10 described a case of significant SOV thrombosis with dural AVF of the ocular vein that was successfully treated by transvenous embolization. In our situation, medical care included the use of anticoagulants, which has been supported by other clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no study has reported arteriovenous shunt disease of the pterygopalatine fossa, but regarding periorbital AVF, for which the hemodynamics and condition often resemble those in the present case, TAE was selected for 27 patients reported by Sato et al and for 10 of 31 patients for whom treatment methods were able to be confirmed from other case reports. [8][9][10][11][12] However, as a complication, visual field defect was observed in three patients. Furthermore, liquid embolic substances may migrate into fine collateral pathways or nerve-nourishing blood vessels that cannot be visualized on angiography, leading to occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…6 Because these lesions are rare, the therapeutic approach to AVFs remains controversial. AVF obliteration has been achieved by conservative management, 7 transcranial surgery, 8 and via endovascular techniques (EVT), including trans-arterial 9 and trans-venous approaches. 3 Although EVT is generally the first choice of intervention, it may occasionally fail, as in the present case.…”
mentioning
confidence: 99%